Correction to: Modeling dysentery spread and the impact of public awareness on control dynamics (Scientific Reports, (2025), 15, 1, (40602), 10.1038/s41598-025-24286-z) - Ahmed, Karim K.; Yusuf, Jibrin Sale; Aliyu, Aliyu Isa; Agaie, Baba Galadima; Yusuf, Abdulrazak Sale; Ozsahin, Ilker; Khalifa, Abeer S. (Nature Research, 2025)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-025-24286-z, published online 18 November 2025 The original version of this Article contained an error in the spelling of the author Ilker Ozsahin which was incorrectly given as Ilker Ozşahin. The original Article has been corrected. © The Author(s) 2025.
Keywords: erratum